Compositional dependence of magnetic damping in sputter-deposited CoxFe1−x thin films - Samanvaya S. Gaur; Rosa E. Diaz; Ernesto E. Marinero (AIP Advances)
Co25Fe75 ferromagnetic films exhibit ultralow magnetic damping. The magnetic damping dependence of Co1−xFex thin films over a Co composition (23%–36%) is reported here. The thin film structures were sputter deposited at ambient temperature, and FMR measurements in both in-plane and out-of-plane geometries were utilized to measure magnetic damping parameters, αtot, which include intrinsic damping and contributions from spin pumping. The damping parameters, αtot, decrease as the Co content is increased, except for Co = 31%. The smallest values of αtot correspond to alloys exhibiting interface perpendicular magnetic anisotropy. A value of ∼0.91 × 10−3 was measured for Co36Fe64, whereas αtot for Co31Fe69 was measured as ∼2.04 × 10−3; this composition exhibits the largest in-plane anisotropy. HAADF-STEM cross section analysis of the Co36Fe64 thin film stack revealed Cu interdiffusion into the magnetic layer. The degree of interdiffusion was found to be up to 7× higher at grain boundaries as compared to the bulk of the polycrystalline grains. The incorporation of Cu into the ferromagnetic layer adversely impacts magnetic damping. Reducing impurities in the magnetic layer by improving the growth chamber base pressure resulted in a reduction of magnetic damping of 18%. The diffraction analysis revealed that the primary growth direction of Co36Fe64 is (101) and that of the Cu buffer layer is (111); these planes are perpendicular to their respective 1̄01 planes, and for this composition, the lattice mismatch was determined to be 0.9325%. The lattice mismatch decreases with increasing Co content and, hence, the lattice strain. The diffusion of Cu into the ferromagnet creates magnon scattering centers and local changes in magnetic properties. Both factors negatively influence magnetic damping. This work is suggestive of potential avenues to further reduce magnetic damping in Co–Fe alloy thin films by controlling the alloy composition, impurities, strain relaxation, and interdiffusion from seed layers, which are required for crystallographic control.